2017
DOI: 10.1177/0974930617732258
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rural Infrastructure on Agricultural Development

Abstract: The present study analysed the effect of rural infrastructure on agricultural development in the southern Indian state of Karnataka. The study used district-level data for 30 years period and employed infrastructure availability and utilisation framework to examine the relationship between the rural infrastructure and agricultural development. The regression analysis showed that infrastructure availability index and infrastructure utilisation index had positive and significant effect on agricultural productivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Better developed rural infrastructure helps save costs of transporting inputs/outputs from/to the markets, which finally increases ROI. The important impacts of rural infrastructure on agricultural development have been discussed in the literature (Charlery et al, 2016;Manjunath & Kannan, 2017). In their investigation of rural India, Manjunath & Kannan (2017) showed that infrastructure availability and infrastructure utilization have a positive and significant effect on agricultural productivity growth.…”
Section: Impact On Roimentioning
confidence: 99%
See 1 more Smart Citation
“…Better developed rural infrastructure helps save costs of transporting inputs/outputs from/to the markets, which finally increases ROI. The important impacts of rural infrastructure on agricultural development have been discussed in the literature (Charlery et al, 2016;Manjunath & Kannan, 2017). In their investigation of rural India, Manjunath & Kannan (2017) showed that infrastructure availability and infrastructure utilization have a positive and significant effect on agricultural productivity growth.…”
Section: Impact On Roimentioning
confidence: 99%
“…The important impacts of rural infrastructure on agricultural development have been discussed in the literature (Charlery et al, 2016;Manjunath & Kannan, 2017). In their investigation of rural India, Manjunath & Kannan (2017) showed that infrastructure availability and infrastructure utilization have a positive and significant effect on agricultural productivity growth. Relative to farmers in Guangdong (reference region), those cultivating banana orchards in Yunnan obtain significantly higher ROI.…”
Section: Impact On Roimentioning
confidence: 99%
“…studies have pointed out that rural infrastructure investment is closely related to the transition period of China's rural economy, and society of the "three rural issues" (Svodziwa, 2018;Bacior and Prus, 2018), will influence the development stage of rural structural transformation of economy (Haggblade et al, 2010); the outdated traffic conditions, science and technology culture and health care have already affected progress of rural structural transformation of the economy (Wu et al, 2017), by investing in rural roads, promoting nonagricultural employment and immigration to urban areas, encouraging the transformation of the rural economic structure (Hine et al, 2019;Sha and Safaie, 2018;Yong and Meiqing, 2017). Existing studies revealed that rural infrastructural investment had obvious positive effect on farmers' income (Manjunath and Kannan, 2017;Zheng, 2017;Lokesha and Mahesha, 2017); however, the income composition of farmers is more complicated; in addition to agricultural income, there are also wage income, transfer income, etc,; the impact mechanism of infrastructure investment on various types of income is bound to be different, but few scholars have divided it for in-depth research (Ghosh, 2017;Ahmad et al, 2016). Although some scholars have pointed out that infrastructure investment is expected to have a positive impact on nonagricultural income, but it will have a negative impact on agricultural income; however, it does not clearly distinguish the impact of different types of infrastructure investment on agricultural income and nonagricultural income, which led to the lack of the explanation to mechanism of action of farmers' income benefited by infrastructural investment.…”
Section: Infrastructural Investment and Farmers' Incomementioning
confidence: 99%
“…According to the Development Bank of Southern Africa (DBSA, 1997), it is important to invest sufficiently in infrastructure as it allows diversification of trade and the country benefits more from globalization. Governments and donors invest heavily in the development of rural roads and transport corridors because investments in rural infrastructure have an important positive effect on agricultural production and trade (Tripathi and Prasad, 2009;Jouanjean, 2013;Manjunath and Kannan, 2017). Adequate and reliable infrastructure provides the physical linkages between different inputs needed for the economy to be functional (Cloete, 2010).…”
Section: Introductionmentioning
confidence: 99%